Improving the Ability of the Teacher’s Training Students in Developing Learning Implementation Plans (RPP) Through Better Teaching and Character Learning Model - Febriyana, Mutia; Winarti, Winarti; Izar, Sri Listiana (Budapest International Research and Critics University, 2021)
This classroom action research aims to improve the ability of the teachers’ training students as teachers in making lesson plans through better teaching and learning character models. This research was conducted in four stages, they are planning, implementing, observing, and reflecting which were carried out in two cycles. In the first cycle, the percentage of students' completeness reached 73.80% with a total of 31 students. Meanwhile, the students were categorized as unfinished was 26.19% with a total of 11 students. Furthermore, in the second cycle, the percentage of the students' completeness reached 92.85% with a total of 39 students. Meanwhile, the students who are categorized as unfinished were 7.14% with a total of 3 students. The improvement of the students' ability in preparing lesson plans for each cycle has increased significantly. This proves that the better teaching and learning character model is able to improve the competence of the teachers’ training students as teachers in preparing learning implementation plans.